expressões populares experienciadas na formação, prática docente e processo criativo - Deu, Sibele Lemes Girvent (2020)
The present work developed through the Professional Master Program Prof- Arts, entitled “Popular Sayings experienced during academic formation, teaching practice and creative process”, is part of the line of research Processes of teaching, learning and creation in arts at the Federal University of Uberlândia, under the guidance of Prof. Dr. Elsieni Coelho da Silva. It a im son popular sayings as a conduit for my practical teacher training and artistic process. Recognizing the insufficiency of research that addresses the forms of oral expression experienced, I make na excerpt that abandons studies that deal with celebrations and religious traditions, focus ingessentially on spoken language. I seek to addres show popular sayings became the instrument for reflections on my training and teaching practice. In general, the objective of this research is to reflecton popular expressions as a source for teacher training and practice in the production of photographic images. Specifically, the objectives of this study are: to develop a personal narrative through a field diary to seek the basis for the reflections of teaching practice; top resent my thoughts on popular sayings in the construction of planning and developments in the daily practice of teachingt the Municipal School Sebastião Rangel in the District of Tapuirama; problematize and reflecton my relationship as a teacher and artist by creating a proposal for experimenting with artistic production with three popular sayings. The present work is conducted in a qualitative way using phenomenology tounderst and my process in pedagogical and artistic practice, permeating the path of narrative writing and guided by ethnography as a way of understanding the popular sayings spoken by students at the Tapuirama’s school. The conclusion of this study seeks to reflecton the relationship between the processes of artistic production, planning and teaching practice as na experience and its resizing.I use a logbook to record my actions, reflections and plans, understanding with Menga (2001) there search from the perspective of its main subjects; I research in Silver (2010) for guidance from words and phrases typically from Minas Gerais and in Urbano (2018) that provides an overview of the language of popular sayings; I use Clandinin and Conelly (2015) tounderst and the reflections derived from the field notebook and conclude with Salles (2000) and the Genetic Criticism to elucidate the artistic path.The hypotheses point to a joint construction of knowledge in dialogue with the affect of the students' senses and my configuration in pedagogical practice.